Inhibition of Spleen Tyrosine Kinase Restores Glucocorticoid Sensitivity to Improve Steroid-Resistant Asthma - Liu, Qian; Hua, Lijuan; Bao, Chen; Kong, Luxia; Hu, Jiannan; Liu, Chao; Li, Ziling; Xu, Shuyun; Liu, Xiansheng (Frontiers in Pharmacology, 2022)
Background: Regulation or restoration of therapeutic sensitivity to glucocorticoids is important in patients with steroid-resistant asthma. Spleen tyrosine kinase (Syk) is activated at high levels in asthma patients and mouse models, and small-molecule Syk inhibitors such as R406 show potent anti-inflammatory effects in the treatment of immune inflammatory diseases. Several downstream signaling molecules of Syk are involved in the glucocorticoid response, so we hypothesized that R406 could restore sensitivity to dexamethasone in severe steroid-resistant asthma. Objective: To discover the role of the Syk inhibitor R406 in glucocorticoid resistance in severe asthma. Methods: Steroid-resistant asthma models were induced by exposure of C57BL/6 mice to house dust mite (HDM) and β-glucan and by TNF-α administration to the bronchial epithelial cell line BEAS-2B. We evaluated the role of the Syk inhibitor R406 in dexamethasone (Dex)-insensitive airway inflammation. Pathological alterations and cytokines in the lung tissues and inflammatory cells in BALF were assessed. We examined the effects of Dex or R406 alone and in combination on the phosphorylation of MAPKs, glucocorticoid receptor (GR) and Syk, as well as the transactivation and transrepression induced by Dex in mouse lung tissues and BEAS-2B cells. Results: Exposure to HDM and β-glucan induced steroid-resistant airway inflammation. The Syk inhibitor R406 plus Dex significantly reduced airway inflammation compared with Dex alone. Additionally, TNF-α-induced IL-8 production in BEAS-2B cells was not completely inhibited by Dex, while R406 markedly promoted the anti-inflammatory effect of Dex. Compared with Dex alone, R406 enhanced Dex-mediated inhibition of the phosphorylation of MAPKs and GR-Ser226 induced by allergens or TNF-α in vivo and in vitro. Moreover, R406 also restored the impaired expression and nuclear translocation of GRα induced by TNF-α. Then, the activation of NF-κB and decreased HDAC2 activity in the asthmatic model were further regulated by R406, as well as the expression of GILZ. Conclusions: The Syk inhibitor R406 improves sensitivity to dexamethasone by modulating GR. This study provides a reference for the development of drugs to treat severe steroid-resistant asthma.